First person - Carina Lund (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Carina Lund is first author on 'Characterization of the human GnRH neuron developmental transcriptome using a GNRH1-TdTomato reporter line in human pluripotent stem cells', published in DMM. Carina is a PhD student in the lab of Taneli Raivio at the University of Helsinki, Finland, investigating neuronal differentiation from human pluripotent stem cells.